Agricultural extension : the training and visit system - Benor, Daniel; Harrison, James Q.; Baxter, Michael; World Bank.; United Nations Development Programme (Washington, D.C., U.S.A. : World Bank, 1984)
This paper has been adopted in either a explicit or implicit form by some forty developing countries in Asia, Africa, Europe, and Central and South America.
"A World Bank and UNDP symposium."
osa 23/01/2019
Loans
Keywords: Agricultural extension work